Relationship between post partum depression with some demographic and ‎psychosocial factors in mothers visiting health – medical centers in city of Rasht - haydeh mahmoodi; naima khodadadi; noshaz mir haghjo; iman taghadosi (Journal of Holistic Nursing and Midwifery)
Introduction: Postpartum depression is a kind of psychiatric disorder that demographic and ‎psychosocial factors are related to it.